The Urgency of Indonesia’s National Security Act: Addressing Fragmentation in Security Sector Regulation - Harefa, Faonaso; Purwanto, Ignatius Eko Djoko; Irwanto, Bambang; Supriyadi, Adang Asep; Saputro, Guntur Eko (Journal of Social Work and Science Education, 2025)
This study examines the urgency of the formation of the National Security Act (Kamnas Law) in Indonesia to overcome the fragmentation of regulations in the security sector. Using statute-based legal approaches (statute-based) and comparative legal approaches, this study found an overlapping gap between institutions such as the TNI, Polri, BNPT, and the Ministry of Defense due to adaptive legal instruments facing multidimensional threats. The absence of coordinative institutions such as the National Security Council (NSC) weakens synergy between institutions. The results of comparisons with countries such as the United States, Singapore, South Korea, and the Philippines show that the centralized security structure has proven effective in integrating defense, intelligence, and law enforcement policies. This study recommends that the Kamnas Law become a comprehensive legal framework to encourage sectoral coordination and institutional synergy in the corridor of democratic government.